Influences of solar energy on the energy efficiency design index for new building ships. (27th July 2017) - Zhu, Yuanqing; Zhou, Song; Feng, Yongming; Hu, Zukang; Yuan, Lu
Abstract: In 2009, Energy Efficiency Design Index (EEDI) of ship was developed to reduce greenhouse gas emissions discharged from ship, and solar energy utilization on the ship can reduce fuel consumption and greenhouse gas emissions of ship. Considering different correlation parameters and energy conversion efficiencies of photovoltaic devices, availability factors of solar energy for new building ships were studied, and the effects of different latitudes, declination angles, hour angles and bevel angles were also analyzed in the paper. With solar energy employing as auxiliary power of ship at 39.1° of north latitude, its energy conservation and emissions reduction value were concluded with the proposed availability factors formula. Solar energy utilization on the ship is proved one pathway to meet the requirement of greenhouse gas emissions discharged from ship by International Maritime Organization (IMO). Highlights: Availability factor of solar energy for new building ships was studied. Availability factors of solar energy under different parameters. Solar energy employed as marine auxiliary power was analyzed. Meeting requirements of IMO EEDI by solar energy utilization on the ship.